RANCANG BANGUN SISTEM REFRIGERATED SEA WATER (RSW) UNTUK KAPAL NELAYAN TRADISIONAL - Budiarto, Untung; Kiryanto, Kiryanto; Firmansyah, Heru (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2013)
Cooling system has been used in the ship, both in comercial or fishing vessel. But it’scontradicts with the traditional fisherman ship of Cukrik type that do not have the particularcooling system to handle the decreasing quality of their catch. The Refrigerated Sea Water(RSW) is used to handle this problem.This research including the step of calculating the power of cooling system thatimportant to determine the component of RSW like a compressor, condensor and evaporator.Than the series of these component are tested in the laboratorium.From this design of cooling system can be obtained the prototype of RSW twhich it simpleto the tradisional fisherman ship of Cukrik type with hold capacity 0,095 m3. when it tested by ittemperature the fish hold without water needed 1 hour to reach 0 oC, than fish hold with seawater needed 7 hour to reach 5 oC. Before applied in a traditional fishing ship so the stabilityanalysis is done by using the software, based on the analysis of the changes in vessel stability isobtained after the RSW system at the point of GZ reduced by 0,012 m, while at this point GMreduced by 0,016 m.